Biological knowledge discovery handbook : preprocessing, mining, and postprocessing of biological data - Elloumi, Mourad; Zomaya, Albert Y. (New Jersey : John Wiley, 2014)
"Molecular biology is undergoing exponential growth in both the volume and complexity of biological data. This book offers the first comprehensive overview of data mining, preprocessing, postprocessing, and storage for biological data. It surveys the latest approaches and techniques in biological KDD, presenting a vast yet detailed view of the most important advances in the field. Combining sound theory, technical depth, and practical applications in molecular biology, Biological Knowledge Discovery is a unique resource for practitioners and researchers in computer science, life science, and mathematics"--
"This book is a survey of the most recent developments on techniques and approaches in the field of biological KDD. It presents the latest, newest, most important topics encountered in this field"--
Includes bibliographical references and index.
Keywords: Bioinformatics; Computational biology; Data mining; COMPUTERS / Database Management / Data Warehousing